P-86 Exposure to pesticides mixture and cancer mortality in banana workers. (14th March 2023) - Barul, Christine; Gambaretti, Juliette; Michineau, Leila; Cabrera, Leila; Spinosi, Johan; Luce, Daniele
Abstract : Introduction: Most of the evidence about the role of occupational exposure to pesticides in cancer is derived from studies where they have been examined in isolation. Moreover, very few studies have been conducted in tropical environments, where unfavourable climatic conditions and pest pressure result in heavier pesticide use than in temperate climate. We aimed to investigate the role of occupational exposure to pesticides mixture in cancer mortality of banana workers. Material and Methods: We used data from a historical cohort of banana workers in the French West Indies, who were followed for mortality from 1981 to 2017. Occupational exposure to pesticides was assessed with a specific crop-exposure matrix. A total of 8 007 subjects who had complete data on occupational exposure to pesticides and cancer mortality were included in the study. Hierarchical clustering on principal component analysis and Cox models were used to define profiles of pesticides exposure and examine their potential role in cancer mortality. Hierarchical Bayesian models allowed investigating the role of exposure to each pesticide in cancer mortality, accounting for the strong correlations between pesticides exposures. Results: Two profiles of exposure emerged among participants low vs heavy users of a fungicides, herbicides, and insecticides mixture. Compared with low users, heavy users of the mixture showed an increased mortality from hematologic malignancies (HR =1.77 95%CI 1.04 to 3.00), and particularly from non-Hodgkin lymphoma (HR =1.83 95%CI 1.01 to 3.34). For the latter, preliminary results on the role of each pesticide exposure, accounting for the others, did not show any association. Conclusion: These findings suggest a deleterious role of occupational exposure to a mixture of pesticides in mortality from hematologic malignancies in banana workers, without any indication of the involvement of a particular pesticide.